A New Numerical Solution Approach for the Real-Time Modeling of Photovoltaic Panels - Can, Hayrettin; Ickilli, Damla; Parlak, Koray Sener (Ieee, 2012)
The growing interest in photovoltaic systems has created a need for test devices required for these systems. PV panel emulators are needed to perform tests on photovoltaic systems and the devices used in them. Basically being DC power supplies, these emulators are controlled to have the same output characteristic as a PV panel and work in real time. The control systems of photovoltaic emulators contain a PV panel model whose accuracy affects the performance of the entire system. Therefore, in creating a PV panel model, mathematical modeling is preferred owing to its high accuracy. In this study, a five-parameter PV panel model has been used. Owing to the transcendental structure of this model, it cannot be analytically solved and requires numerical methods. The number of numerical iterations is rather important to the computational speed of the PV panel model and the numerical convergence time. Thus, real-time systems need to start with a well-suited initial value for iteration. This study proposed a new method for the initial value of numerical solution, and obtained rather favorable results compared to the other methods cited in the literature.
Asia-Pacific Power and Energy Engineering Conference (APPEEC) -- MAR 27-29, 2012 -- Shanghai, PEOPLES R CHINA
Keywords: PV panel emulator; photovoltaic panel; Newton's Method; mathematical model; real time modeling